Susceptibility and barriers to infection of Colorado mosquitoes with Rift Valley fever virus - Hartman, Daniel A.; Bergren, Nicholas A.; Kondash, Therese; Schlatmann, William; Webb, Colleen T.; Kading, Rebekah C. (PLOS Neglected Tropical Diseases, 2021)
Author summary Rift Valley fever virus (RVFV) causes morbidity and mortality in humans and domestic ungulates in sub-Saharan Africa, Egypt, and the Arabian Peninsula. Mosquito vectors transmit RVFV between vertebrates by bite, and also vertically to produce infectious progeny. To inform vector control priorities upon the introduction of RVFV to the United States, we tested the ability of three floodwater Aedes species known to feed on cattle and/or deer in Colorado (Aedes vexans [Meigen], Aedes melanimon Dyar, Aedes increpitus Dyar) to transmit RVFV (vector competence). We also tested Culiseta inornata (Williston), and Culex tarsalis Coquillett which exhibits high vector competence, and the potential for vertical transmission by testing ovaries. These data were modeled to estimate the potential for virus transmission, based on the infection probabilities of different organs that serve as transmission barriers inside the mosquitoes. The permanent-water-breeders Cs. inornata and Cx. tarsalis exhibited higher efficiency of horizontal transmission as well as potential vertical transmission. Aedes species were less efficient at vertical and horizontal transmission, with high barriers to infection of and dissemination from the midgut. Overall, these data support the transmission of RVFV by a broad range of potential vectors in the United States, posing a major challenge for vector control if this virus is introduced.